Accountability and the internet - Crowther, David; Rayman-Bacchus, Lez (Managerial auditing journal ; v, 2003)
It would not be an exaggeration to claim thatthe Internet is now ubiquitous, playing asubstantial role in both our personal andprofessional lives. IT industry observers andpractitioners alike regard the emergence ofthe Internet as having the same influence onsociety today as the development ofelectricity had on our forefathers a centuryago.